Analysis of influencing factors on the soil arching effect of anti-slide piles in reservoir bank landslides - Zhou, Chunmei; Qin, Zihan; Li, Guangbo; Xing, Haiguang (Frontiers in Earth Science, 2025)
Anti-slide piles are widely used for landslide mitigation, providing an effective engineering solution for slope protection. A critical factor in the design and performance of these structures is the soil arching effect, which arises from the interaction between anti-slide piles and the surrounding soil. This study explores the factors influencing the development of the soil arching effect, using both a mechanical equilibrium model and finite element numerical simulations. Specifically, the study examines the impact of landslide thrust magnitude, pile embedment depth, and the number of wet-dry soil cycles on the soil arching effect. The results show that there is an optimal range of landslide thrust within which the soil arching effect develops fully. The degree of the soil arching effect initially decreases but then increases as the pile embedment depth increases. Furthermore, under the influence of wetting-drying cycles, the soil arching effect undergoes an initial weakening phase, followed by a subsequent strengthening stage, and ultimately culminates in failure at a specific depth. The study proposes a composite evaluation framework utilizing the thrust-to-cohesion ratio and stress homogenization index within arching zones as robust discriminators for quantifying arching development stages. These findings provide important insights for the design of anti-slide piles and the long-term stability of landslide mitigation efforts.